2012
DOI: 10.1007/s10863-012-9456-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynonenal, a lipid peroxidation end product, stimulates uncoupling protein activity in Acanthamoeba castellanii mitochondria; the sensitivity of the inducible activity to purine nucleotides depends on the membranous ubiquinone redox state

Abstract: We studied the influence of exogenously generated superoxide and exogenous 4-hydroxy-2-nonenal (HNE), a lipid peroxidation end product, on the activity of the Acanthamoeba castellanii uncoupling protein (AcUCP). The superoxide-generating xanthine/xanthine oxidase system was insufficient to induce mitochondrial uncoupling. In contrast, exogenously added HNE induced GTP-sensitive AcUCP-mediated mitochondrial uncoupling. In nonphosphorylating mitochondria, AcUCP activation by HNE was demonstrated by increased oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The discussion was recently extended to the uncoupling protein of unicellular eukaryotes. Woyda-Ploszczyca and Jarmuszkiewicz demonstrated that HNE activates UCP in Acanthamoeba castellanii mitochondria during non-phosphorylating respiration [24].…”
Section: Introductionmentioning
confidence: 99%
“…The discussion was recently extended to the uncoupling protein of unicellular eukaryotes. Woyda-Ploszczyca and Jarmuszkiewicz demonstrated that HNE activates UCP in Acanthamoeba castellanii mitochondria during non-phosphorylating respiration [24].…”
Section: Introductionmentioning
confidence: 99%
“…This explanation does not exclude HNE-induced UCP-mediated uncoupling effect after the drop of Δ Ψ during oxidative phosphorylation. Moreover, in mammalian, plant, and amoeba mitochondria Smith et al , 2004 ;Woyda -Ploszczyca and Jarmuszkiewicz, 2012 ), the HNE-induced UCP-mediated proton leak is still observed at Δ Ψ values close to those of phosphorylating conditions in flux-force relationships.…”
Section: Discussionmentioning
confidence: 92%
“…Because the effect of HNE is highly sensitive to GTP, as confirmed in the present work for the UCP of a unicellular organism, HNE may bind reversibly to UCP in a PN-dependent manner. When A. castellanii and mammalian mitochondria have been incubated with HNE and PNs, the stimulation of UCP by HNE could be almost fully prevented Woyda -Ploszczyca and Jarmuszkiewicz, 2012 ). Moreover, in A. castellanii mitochondria, the inhibitory effect of GTP on the HNE-induced AcUCP-mediated uncoupling can be only observed when Q is sufficiently oxidized.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations